Advanced 3D bioprinted liver models with human-induced hepatocytes for personalized toxicity screening - Yue Ma; Runbang He; Bo Deng; Miaomiao Luo; Wenjie Zhang; Lina Mao; Wenxiang Hu; Yilei Mao; Huayu Yang; Pengyu Huang (Journal of Tissue Engineering)
The development of advanced in vitro models for assessing liver toxicity and drug responses is crucial for personalized medicine and preclinical drug development. 3D bioprinting technology provides opportunities to create human liver models that are suitable for conducting high-throughput screening for liver toxicity. In this study, we fabricated a humanized liver model using human-induced hepatocytes (hiHeps) derived from human fibroblasts via a rapid and efficient reprogramming process. These hiHeps were then employed in 3D bioprinted liver models with bioink materials that closely mimic the natural extracellular matrix. The constructed humanized 3D bioprinted livers (h3DPLs) exhibited mature hepatocyte functions, including albumin expression, glycogen storage, and uptake/release of indocyanine green and acetylated low-density lipoprotein. Notably, h3DPLs demonstrated increased sensitivity to hepatotoxic agents such as acetaminophen (APAP), making them a promising platform for studying drug-induced liver injury. Furthermore, our model accurately reflected the impact of rifampin, a cytochrome P450 inducer, on CYP2E1 levels and APAP hepatotoxicity. These results highlight the potential of hiHep-based h3DPLs as a cost-effective and high-performance alternative for personalized liver toxicity screening and preclinical drug testing, paving the way for improved drug development strategies and personalized therapeutic interventions.